SURGICAL OPTIONS FOR ANTERIOR ABDOMINAL WALL HERNIAS AND ABDOMINOPOTOSIS (LITERATURE REVIEW) (World Bulletin of Public Health, 2024)
Correction of anterior abdominal wall deformities is one of the most common surgical interventions in the modern practice of a plastic surgeon. However, this method is still not fully resolved. Thus, new methods of surgical correction appear and old ones are improved. Each physician chooses an approach to solve the problem of restoring the aesthetic contours of the anterior abdominal wall and meeting the needs of the patient. According to the American Society of Plastic and Reconstructive Surgeons, abdominoplasty is the fifth most common among aesthetic plastic surgeries to correct deformities and defects of the anterior abdominal wall caused by abdominoptosis
Keywords: surgical treatment; abdominophotosis; front abdominal hurricane